Implementation of CRM Method as a Business Strategy of Jangek Fauzi's Home Industry - Rizki, Muhammad; Anggraeni, Dewi; Akmal, Akmal (Sinkron : jurnal dan penelitian teknik informatika, 2022)
:   Home Industry Jangek Fauzi Crackers is a home industry that produces jangek crackers, where the products will be marketed and sold in various places such as shops and stalls. Home Industry Crackers Jangek Fauzi continues to try to expand its target market outside the city. Ordering jangek crackers here is still done manually. To achieve its goal, Jangek Fauzi Cracker Home Industry needs a website. Currently at Home Industry Crackers Jangek Fauzi in making sales reports is still manual using the excel application so that the processing of sales report data is still slow and not detailed. Currently, Jangek Fauzi Crackers Home Industry does not have specific activities or strategies that handle marketing, product marketing is done conventionally by means of customers providing information about places, features and products to other potential customers. Dissemination of ineffective information makes customers not aware of the latest information on the Home Industry of Jangek Fauzi Crackers, thus influencing customers to switch to other factories. With a website using the Customer Relationship Management (CRM) method, the data storage process can be more accurate and neatly stored and the making of sales reports will be fast and timely and the delivery of promotional information will be faster and the response to sales will be faster.